Mitochondria-Associated Endoplasmic Reticulum Membranes in the Pathogenesis of Type 2 Diabetes Mellitus - Yang, Shanshan; Zhou, Ruixue; Zhang, Caixia; He, Siyuan; Su, Zhiguang (Frontiers in Cell and Developmental Biology, 2020)
The endoplasmic reticulum (ER) and mitochondria are essential intracellular organelles that actively communicate via temporally and spatially formed contacts called mitochondria-associated membranes (MAMs). These mitochondria-ER contacts are not only necessary for the physiological function of the organelles and their coordination with each other, but they also control intracellular lipid exchange, calcium signaling, cell survival, as well as homeostasis in cellular metabolism. Growing evidence strongly supports the role of the mitochondria-ER connection in the insulin resistance of peripheral tissues, pancreatic β cell dysfunction, and the consequent development of type 2 diabetes mellitus (T2DM). In this review, we summarize current advances in the understanding of the mitochondria-ER connection and specifically focus on addressing a new perspective of the alterations in mitochondria-ER communication in insulin signaling and β cell maintenance.